A Software Design of on Board Display System Based on QNX - 匡晋湘; 刘辉 (机车电传动)
Based on the analysis of functional requirements for on board display system, an application software design structure with high availability was proposed according to the high modular application system and good graphic-development environment of QNX operating software. The design structure divided software into several modules so as to realize the data transmission between modules and the module management by messages, which is an important technical measure of optimizing efficiency and reliability.